2018
DOI: 10.1101/365619
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell transcriptomics characterizes cell types in the subventricular zone and uncovers molecular defects underlying impaired adult neurogenesis

Abstract: Neural stem cells (NSCs) contribute to plasticity and repair of the adult brain. Niches harboring NSCs are crucial for regulating stem cell self-renewal and differentiation. We used single-cell RNA profiling to generate an unbiased molecular atlas of all cell types in the largest neurogenic niche of the adult mouse brain, the subventricular zone (SVZ). We characterized > 20 neural and non-neural cell types and gained insights into the dynamics of neurogenesis by predicting future cell states based on computati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…Our analyses provide a molecular characterization of the NSC transition to and from dormancy. Consistent with other studies of quiescent stem cells (reviewed in van Velthoven and Rando, 2019), including quiescent adult NSCs (Llorens-Bobadilla et al, 2015;Mizrak et al, 2019;Kalamakis et al, 2019;Zywitza et al, 2018;Basak et al, 2018;Dulken et al, 2017;Shin et al, 2015;Berg et al, 2019;Hochgerner et al, 2018;Artegiani et al, 2017), our data indicate that dormancy involves a broad dampening of cell biological processes associated with an active state. As embryonic RPs transitioned to postnatal dNSCs, they shut down processes associated with cell division, transcription, RNA metabolism and protein translation, processing, and trafficking.…”
Section: Figure 7 Similarities Between Adult Taps and E14 Ge Rpssupporting
confidence: 92%
“…Our analyses provide a molecular characterization of the NSC transition to and from dormancy. Consistent with other studies of quiescent stem cells (reviewed in van Velthoven and Rando, 2019), including quiescent adult NSCs (Llorens-Bobadilla et al, 2015;Mizrak et al, 2019;Kalamakis et al, 2019;Zywitza et al, 2018;Basak et al, 2018;Dulken et al, 2017;Shin et al, 2015;Berg et al, 2019;Hochgerner et al, 2018;Artegiani et al, 2017), our data indicate that dormancy involves a broad dampening of cell biological processes associated with an active state. As embryonic RPs transitioned to postnatal dNSCs, they shut down processes associated with cell division, transcription, RNA metabolism and protein translation, processing, and trafficking.…”
Section: Figure 7 Similarities Between Adult Taps and E14 Ge Rpssupporting
confidence: 92%
“…To further analyze the epidermal differentiation dynamics in UW skin, we performed RNA velocity analysis, in which the direction of state transitions and the extent of change in RNA dynamics are indicated by the vectors (arrows) and their lengths, respectively (La Svensson and Pachter, 2018). The Col17a1 Hi and SP1 states showed small RNA velocities (short or no arrows), known to associate with both quiescent and terminally differentiated cells (Svensson and Pachter, 2018;Zywitza et al, 2018), whereas the ER, GA, and SP2 states exhibited large RNA velocities (Figure 7F). Transition from the Col17a1 Hi state to the ER state was associated with increasing arrow lengths, which may reflect a rapid activation in RNA dynamics (e.g., increased RNA splicing efficiency; see below).…”
Section: Pseudotemporal Trajectory and Rna Velocity Analyses Reveal Basal Cell State Transition Dynamics And Wound-induced Cellular Plastmentioning
confidence: 99%
“…Astrocytes close to the lesion form Ascl1-expressing transit-amplifying cells before generating proliferative clusters of doublecortin (Dcx) + neuroblasts and mature neurons. Single-cell RNA sequencing (scRNA-seq) revealed that conditional knockout of Rbpj-k drives induction of a neural stem cell program in cortical astrocytes that resembles canonical neurogenic processes, as observed in transcriptome analyses of the germinal niche (Llorens-Bobadilla et al, 2015;Zywitza et al, 2018). However, only after a stab wound injury can the neurogenic program be instigated, and Notch-deficient cortical astrocytes are able to progress through amplifying cell divisions to generate GABAergic interneurons.…”
Section: Introductionmentioning
confidence: 99%